REPRESENTASI MEDIA DAKWAH MODERN: STUDI KASUS PADA PLATFORM TWITTER - Anggia Kesuma Putri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Twitter is the most widely used social media platform by millennials in the digital era. One of the positive things that can be utilized is the potential of Twitter as a medium of da'wah, especially for the millennial generation. With the advantage of being able to upload writing in a relatively short time so that it can reach all groups. One of the most famous preachers today, Husen Ja'far, who uses his Twitter account for da'wah media with 713 thousand followers. This study aims to conduct a semiotic analysis of Husein Ja'far's account comments and how Twitter is used as a representation of da'wah media in the digital era. This study uses Charles Sanders Pierce's semiotic analysis model. The sampling technique in this study used simple random sampling. Data collection techniques used by researchers are document analysis and literature study. This study analyzes the responses of Twitter netizens regarding da'wah content uploaded by the @Husen_Jafar account. The results of the study show that there are three signs that form the basis of the researcher's analysis on Husen Ja'far's account. The first is a sign of the many comments that appear in every upload of Husen Ja'far, although the number varies. The second netizen expressed his gratitude for the knowledge that had been shared in Husein Ja'far's upload. And finally, there is a follow-up question regarding Husein Ja'far's explanation of a religious issue.